The Human Face Becomes Mapped as a Sensorimotor Reaching Space During the First Year. Issue 2 (30th July 2020) - Chinn, Lisa K.; Noonan, Claire F.; Lockman, Jeffrey J.
Abstract : Although recent behavioral and neural research indicates that infants represent the body's structure, how they engage self‐representations for action is little understood. This study addressed how the human face becomes a reaching space. Infants ( N  = 24; 2–11 months) were tested longitudinally approximately every 3 weeks on their ability to reach to a vibrating target placed at different locations on the face. Successful reaches required coordinating skin‐ and body‐based codes for location, a problem known as tactile remapping. Findings suggest that a functional representation of the face is initially fragmented. Infants localized targets in the perioral region before other areas (ears/temples). Additionally, infants predominantly reached ipsilaterally to targets. Collectively, the findings illuminate how the face becomes an integrated sensorimotor space for self‐reaching.